Demographic Factors, Antibiotic Resistance, and Resistance Gene Prevalence in Klebsiella Pneumoniae-Associated Urinary Tract Infections - Mahmood, Mohammed Khamees; Özdeniz, Dr. Ebru (American Journal of Biology and Natural Sciences, 2024)
This study investigated the prevalence of Klebsiella pneumoniae in urinary tract infections, its associated antibiotic resistance patterns, and resistance genes in a specific population. Klebsiella. pneumoniae was found to be a significant pathogen, particularly among older adults (52.5% in the 50-69 years age group), females (64.4%), and individuals residing in rural areas 59.3%). The isolates exhibited high resistance to multiple antibiotics, including carbapenems, and notably, the highest resistance rate was Amikacin (84.7%), followed by Imipenem (79.7%), Ceftriaxone (76.3%), and Cefotaxime (74.6%). Moderate resistance was found against Meropenem (69.5%), Lincomycin (64.4%), Trimethoprim (57.6%), and Tobramycin (40.7%). The lowest resistance rates were seen against Chloramphenicol (35.6%), Erythromycin (30.5%), Oxacillin (25.4%), and Azithromycin (12%). Molecular analysis revealed the presence of resistance genes, such as bla-OXA-1 (72.9%), bla-CTX-M (49.2%), rmtC (54.2%), and lower prevalence was observed with armA (28.8%), contributing to the observed resistance. These findings highlight the urgent need for effective strategies to combat the rising threat of antibiotic-resistant K. pneumoniae infections.